The Hyperphagia Questionnaire: Insights From a Multicentric Validation Study in Individuals With Prader Willi Syndrome - Maria Rosaria Licenziati; Dario Bacchini; Antonino Crinò; Graziano Grugni; Danilo Fintini; Sara Osimani; Letizia Ragusa; Michele Sacco; Lorenzo Iughetti; Luisa De Sanctis; Adriana Franzese; Malgorzata Gabriela Wasniewska; et al. (Frontiers Media S.A., 2022)
Background/ObjectivesThe present study aimed to validate the Italian version of the Hyperphagia Questionnaire (HQ), a 11-items questionnaire developed to assess hyperphagia in individuals with Prader-Willi syndrome (PWS). This is a complex neurodevelopmental disorder characterized by endocrine dysfunction, hypotonia, intellectual disability, psychiatric disorders and obesity.MethodsParents of 219 individuals with PWS (age range 3-54 years; Mage = 17.90; 108 Males), recruited in 12 hospitals in Italy responded to HQ during routine visits. In function of the level of analyses the sample was divided into two subgroups (<18> years) or into four age-subgroups (2.5-4.5; 4.5-8; 8-18; >18 years) corresponding to different clinical stages.ResultsConfirmatory factor analysis (CFA) confirmed the three hyperphagic subdimensions of the original structure (behavior, drive, and severity), but one item was dropped out, reducing the final version to 10 items. Using multi-group CFA, HQ showed satisfactory indexes of measurement invariance by age. Good indexes of internal consistency (Cronbach's alpha and McDonald's Omega coefficients) were found for each subdimension. The three hyperphagia subdimensions positively converged with other food-related measures: emotional overeating, food enjoyment, food responsiveness, and satiety responsiveness. A significant increase of all hyperphagic subdimensions was found across age groups. Higher hyperphagic levels were found in participants with higher body mass index. Hyperphagic drive differently increased in function of the interaction between age and underlying genetic mechanisms.ConclusionThe Italian version of the HQ is a psychometrically valid and reliable instrument for assessing hyperphagia in individuals with PWS. This tool may prove useful to evaluate the efficacy of pharmacologic and rehabilitative treatments.